OPTIMALISASI PERAN PEMERINTAH DAERAH DALAM MENJADIKAN DESA PONTEH SEBAGAI DESA UMKM - Syaiful Anam; Mohammad Fahrur Rozi; Marsum Marsum (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Micro, small and medium business (MSME) activities are one of the business fields that can develop and are consistent in the national economy. Micro, small and medium enterprises (MSMEs) are a good place for the creation of jobs planned by the government, private sector and Village, Galis District, Pamekasan Regency individual business actors. Micro, Small and Medium Enterprises (UMKM) at Ponteh expands fastly. A lot of business create larger job opportunity in order to reduce unemployment people. One of the idea on empowering UMKM in information technology era is by establishing central communication of UMKM based on Website. By making web marketing media, besides it provides information about UMKM development in Ponteh, it can be functioned to access for any information of production factors. In addition, it can communicate with another UMKM globally to extend the networks. But some employers are constrained by rising raw material prices, the limited of human resources, has a problem in the capital, lack of infrastructure and lack of access to product marketing.